Thinking big for smallholder agriculture: realizing agricultural potentials in changing times - Prager, Steven; Schiek, Benjamin E.; Petsakos, Athanasios; Kruseman, Gideon K.; Gbegbelegbe, Sika; Terheggen, Anne; Mason-D'Croz, Daniel (2021)
Recent advances in approaches to quantitative strategic foresight have enabled new insights into understanding potential futures of the agriculture sector. Quantitative foresight approaches facilitate understanding of different plausible scenarios, especially as related to both endogenous and exogenous factors (e.g., global markets and climate change). These approaches tend to be macroeconomic in nature and resolve trends relative to coarse-grained drivers. In order translate these outputs into strategies that realistically benefit producers across scale, finer resolution and context specific understanding is needed. This paper offers perspective on how foresight analysis can be combined with more pointed assessment of the specific policies, institutions and market requirements needed create more inclusive agricultural investment strategies.